Syntactic foam under compressive stress: Comparison of modeling predictions and experimental measurements. (May 2021) - Paget, Baptiste; Zinet, Matthieu; Cassagnau, Philippe
Syntactic foams are composite materials consisting in the association of hollow particles, called "microspheres" and a polymer matrix. The use of soft shell microspheres confers to the foam interesting properties but in return increases significantly its compressibility. Therefore, understanding and predicting the relationship between pressure and volume change is a crucial issue for the development of this type of material. The present study focuses on a high void fraction syntactic foam made with soft shell polymer microspheres embedded in a polyurethane matrix. Compression tests are performed using a capillary rheometer and a PVT accessory for the hydrostatic compression, and a more conventional apparatus for the confined compression. The experimental results are compared with De Pascalis's pressure/volume model predictions, using Fok and Allwright's model to determine the critical buckling pressure of the microspheres. The model proves to be fairly accurate at low pressure and high pressure, despite a notable deviation in the mid-pressure range. The influence of key model parameters such as microsphere size distribution and microsphere and matrix elastic properties is investigated. It is shown that the reinforcement of the matrix seems to be the only efficient way to limit the compressibility of such a syntactic foam.